PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SCRATCH UNTUK MENINGKATKAN PHYSICS IDENTITY DAN LITERASI SAINS - Cahyaningrum Solehati (UIN Sunan Gunung Djati Bandung, 2026)
Students’ understanding of physics concepts is often constrained by the abstract nature of the material and the lack of connection to real life contexts. The use of digital media that combines interactive visual with local culture element, such as the traditional procces of making geplak, can be a solution to improve students engagement and conceptual understanding. This study aims to develop Scratch-based interactive physics learning media integrated wit tradional geplak in the topic of heat and temperature, as well as to asses its feasibility and effectiveness in improving students’ scientific literacy and physics identity. This research is a type of research and development ( R & D) using the 4D model (Define, Design, Develop, Disseminate). The validation results showed that the developed media was categorized as highly feasible., with an average score of 90,67%. The results also indicated that the media was effective in improving scinetific literacy and in fostering students physics idnetity